Association between liver fibrosis scores and short-term clinical outcomes in hospitalized chronic kidney disease patients: a prospective observational study - Das, Dhriti Sundar; Anupam, Anurag; Saharia, Gautom Kumar (Frontiers in Medicine, 2024)
In resource-constrained countries, inadequate access to healthcare and prognostic tools can be the Achilles' heel in effectively managing Chronic Kidney Disease (CKD).There is significant similarity in the pathogenesis of CKD and liver fibrosis. The role of liver fibrosis (LF) scores predicting the short term clinical outcomes in hospitalized patients with CKD is unknown. Our study aimed at calculating LF scores and studying association of liver fibrosis with short term mortality and morbidity in CKD patients.Patients above 15 years with CKD were enrolled.LF scores namely NFS, GPRI and FIB-4 scores were calculated. Patients were followed up for a period of 28 days for good and poor composite outcome namely requirement of hemodialysis, non-invasive ventilation, prolonged hospital stay, neurological and cardiovascular outcome including death).Among 163 patients, 70.5% were below 60 years of age and 82.2% were male. 35% were diabetic and 52.1% had poor composite outcome at 28 day follow up. The AUROC for GPRI and FIB4 predicting poor outcome was 0.783 (95% CI: 0.71 -0.855) (p < 0.001) and 0.62 (95% CI: 0.534 -0.706) (p = 0.008) respectively. The AUROC for GPRI and NFS predicting allcause mortality was 0.735 (95% CI: 0.627 -0.843) (p = 0.001) and 0.876 (95% CI: 0.8 -0.952), (p <0.001) respectively.We found a positive association between LF scores and CKD outcome in hospitalized patients. The LF scores significantly predicted poor outcome in patients with CKD. Amongst the scores, GPRI was found to be a stronger predictor in predicting outcome in both diabetic and nondiabetic patients with CKD. High GPRI score was also associated with poor outcome and increased mortality in both diabetics and non-diabetics.1.This is the only study till date to our knowledge which used liver fibrosis scores to study the short term clinical outcome in CKD patients.2. In this study, multiple clinical outcomes were studied 3. Clinical outcomes were observed in both diabetics and non-diabetics and were evaluated separately.4.The study was conducted on a relatively small sample size of 163 patients.5. Although all liver disease patients were excluded in the study but underlying subclinical liver diseases cannot be ruled out which may have affected the outcomes.